2020
DOI: 10.3390/ijms22010179
|View full text |Cite
|
Sign up to set email alerts
|

The Dual Role of Autophagy in Cancer Development and a Therapeutic Strategy for Cancer by Targeting Autophagy

Abstract: Autophagy is a delicate intracellular degradation process that occurs due to diverse stressful conditions, including the accumulation of damaged proteins and organelles as well as nutrient deprivation. The mechanism of autophagy is initiated by the creation of autophagosomes, which capture and encapsulate abnormal components. Afterward, autophagosomes assemble with lysosomes to recycle or remove degradative cargo. The regulation of autophagy has bipolar roles in cancer suppression and promotion in diverse canc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
71
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 116 publications
(72 citation statements)
references
References 188 publications
(214 reference statements)
1
71
0
Order By: Relevance
“…p53, Bcl-2/Beclin 1, Atg proteins, p62 or caspases are the key factors connecting apoptosis and autophagy. As it was mentioned above caspases are engaged in both extrinsic and intrinsic apoptotic pathways, but also affect the autophagy process [ 47 ]. Oral et al demonstrated that overexpression of caspase-8 promotes the degradation of Atg3 protein and finally inhibits its pro-autophagic activity [ 48 ].…”
Section: Discussionmentioning
confidence: 99%
“…p53, Bcl-2/Beclin 1, Atg proteins, p62 or caspases are the key factors connecting apoptosis and autophagy. As it was mentioned above caspases are engaged in both extrinsic and intrinsic apoptotic pathways, but also affect the autophagy process [ 47 ]. Oral et al demonstrated that overexpression of caspase-8 promotes the degradation of Atg3 protein and finally inhibits its pro-autophagic activity [ 48 ].…”
Section: Discussionmentioning
confidence: 99%
“…Autophagy has dichotomous roles in tumor promotion and suppression. In the early stages of cancer progression, autophagy acts as a tumor suppressor by removing damaged proteins and organelles, inhibiting inflammation, limiting genomic instability, inducing stress, and suppressing ROS production by the mitochondria (Lim and Murthy, 2020;Yun et al, 2020). In contrast, when tumors are already established, autophagy promotes cancer cell survival and growth by reprogramming metabolism, promoting angiogenesis, and promoting hypoxia and oxidative stress (Das et al, 2018;Thomas et al, 2018).…”
Section: Autophagy Triggeringmentioning
confidence: 99%
“…Autophagy, as a ubiquitous survival pathway in cells, is closely linked with cancer, in which it plays a dual role as either a tumor suppressor or a tumor promoter ( Yun et al, 2021 ). In the early stage of tumorigenesis, autophagy maintains cellular homeostasis through protein and organelle quality control mechanisms ( Li et al, 2020 ).…”
Section: The Physiological Roles Of Autophagy In Different Adult Stem Cells and Related Diseasesmentioning
confidence: 99%